Analisis Pengaruh Return On Asset Dan Return On Equity Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur Sub Sektor Kimia Periode 2021 - Akbar Dwi Antono; Karnila Ali; Sri Retnaning Rahayu (Jurnal Manajemen DIVERSIFIKASI, 2025)
Dividend policy is a decision whether to distribute profits earned by the company to shareholders as dividends, or keep them as retained earnings to finance future investments. This research used descriptive quantitative approach which the aims to determine there is an effect of Return On Assets (ROA) and Return on Equity (ROE) on dividend policy. The samples in this research used 9 chemical manufacturing companies in the chemical sub-sector for the 2021 period. The results of the analysis show that Return On Assets (ROA) has a positive effect on dividend policy with a regression coefficient of the ROA variable (X1) of 5437703402.135, which means that ROA has increased by 1 % then the dividend policy (Y) will increase in value by Rp. 5437703402,135. Meanwhile, Return On Equity (ROE) has a negative effect with the regression coefficient of the ROE variable (X2) of -10050755397.989, which means that if ROE increases by 1%, the dividend policy (Y) will experience a decrease in value of Rp.-10050755397.989 on dividend policy in chemical sub-sector manufacturing companies for the 2021 period listed on the Indonesian Stock Exchange (IDX).